Emerging trends, techniques, and tools for massive open online course (MOOC) management - Queirós, Ricardo 1975- (IGI Global, 2018)
"This book addresses the difficulties and challenges in the MOOC design, implementation, management and deployment. It focuses on different aspects of the MOOC life-cycle process and explores the impact of new methodologies and frameworks used in the life cycle of a MOOC ranging from well-designed synchronous virtual classrooms to assessment, gamification and collaborative services and tools"...
Keywords: MOOCs (Web-based instruction); Distance education; Educational technology